2015
DOI: 10.1016/j.jtcvs.2015.01.014
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive aortic valve replacement provides equivalent outcomes at reduced cost compared with conventional aortic valve replacement: A real-world multi-institutional analysis

Abstract: Background Several single center studies have reported excellent outcomes with minimally invasive aortic valve replacement (mini-AVR). Although criticized as requiring more operative time and complexity, mini-AVR is increasingly performed. We compared contemporary outcomes and cost of mini-AVR versus conventional AVR in a multi-institutional regional cohort. We hypothesize that mini-AVR provides equivalent outcomes to conventional AVR without increased cost. Methods Patient records for primary isolated AVR (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
66
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(76 citation statements)
references
References 25 publications
5
66
0
5
Order By: Relevance
“…Minimally invasive AVR has been associated by majority of authors with better perioperative outcomes [5,6,8,10,13], but constantly longer operative times, compared to full sternotomy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Minimally invasive AVR has been associated by majority of authors with better perioperative outcomes [5,6,8,10,13], but constantly longer operative times, compared to full sternotomy.…”
Section: Discussionmentioning
confidence: 99%
“…have been developed for AVR since 1993 [1][2][3][4] and have been associated with better outcomes and lower perioperative morbidity compared to full sternotomy [5][6][7][8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, Cosgrove and Cohn were the first clinicians to pioneer smaller incisions for both mitral and aortic procedures (1). Despite longer cardiopulmonary bypass (CPB) times compared to conventional surgery (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12), preservation of the sternal integrity and minimisation of dissection had been advocated to improve the cosmetic result, reduce bleeding, provide better respiratory function, yield shorter hospital stays and therefore lower costs and improved patient satisfaction. A large meta-analysis by Phan et al demonstrated that minimally invasive AVR (mini-AVR) is also associated with a reduced incidence of renal failure and has comparable mortality and morbidity to conventional surgery (13).…”
Section: Introductionmentioning
confidence: 99%
“…
Протезування аортального клапана (ПАК) через традиційно використовувану серединну стернотомію є безпечною і рутинною процедурою з низьким ризи-ком і відмінними довгостроковими результатами [1].Однак з плином часу й удосконаленням опера-тивної техніки з'явилася потреба у зменшенні хірур-гічної агресії з метою мінімізації операційної травми та виникнення ускладнень, пов'язаних зі стандарт-ною стернотомією [2].Досягнуті хороші результати ПАК завдяки постій-ному вдосконаленню хірургічної техніки та застосу-ванню більш досконалих новітніх технологій дозво-ляють виконувати операції з меншою травматичністю для пацієнта. У цьому сенсі важливим є впроваджен-ня мінімально інвазивних доступів (МІД), оскільки це сприяє прискоренню одужання пацієнта за раху-нок більш швидких темпів його відновлення [3].

Незважаючи на короткий час з початку розвитку нового напрямку, на сьогодні вже накопичений ве-ликий світовий досвід щодо застосування мінімаль-но інвазивних доступів у хірургічній корекції вад аортального клапана [4][5][6].

За сучасними науковими уявленнями, інтервен-ція будь-якого патогенного чинника в організм, у тому числі й операційна травма, супроводжується розвитком в організмі хворого системної запаль-ної реакції (СЗР), дія якої спрямована на усунення наслідків впливу ушкоджувального етіологічного чинника, патофізіологічних і патобіохімічних пору-шень, на відновлення функцій органів, що постраж-дали [7][8][9].

У разі адекватної СЗР з часом настає одужання, а у разі неадекватного її перебігу з гіперпродукцією медіаторів запалення, з порушенням балансу між запальними і протизапальними медіаторами ця ре-акція організму може привести до розвитку синдро-му поліорганної дисфункції [9][10][11].

З огляду на це цілком логічно припустити, що зменшення операційної травми шляхом мініміза-

…”
unclassified
“…Однак з плином часу й удосконаленням опера-тивної техніки з'явилася потреба у зменшенні хірур-гічної агресії з метою мінімізації операційної травми та виникнення ускладнень, пов'язаних зі стандарт-ною стернотомією [2].…”
unclassified